Diskriminasi, Kekerasan, dan Ketidakadilan Gender di Tempat Kerja: Analisis Manajemen Sumber Daya Manusia pada Industri Nikel - Dea Rindha Seftiana; Sivi Nova Setyorini; Nur Indah Ageng Setiani; Rafika Meilia Sari (J-MSDM (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2026)
This study aims to analyze discrimination, violence, and gender inequality against female workers in the nickel industry from a human resource management perspective. This study employs a qualitative approach using literature review and content analysis methods. Research data were obtained from news articles, scientific journals, official agency reports, and documents related to gender and labor issues. The results indicate that female workers in the nickel industry continue to face marginalization, gender bias, subordination, limited career opportunities, and vulnerability to sexual violence in the workplace. Human resource management functions also remain suboptimal, as recruitment practices, compensation, labor protection, and promotion processes are still influenced by patriarchal culture and gender stereotypes. The primary factors perpetuating gender inequality are the dominance of masculine culture, weak protections for female workers, and a lack of gender-responsive organizational policies. This study concludes that more inclusive and gender-responsive human resource management policies are needed to create a safe, fair, and gender-equitable work environment in the nickel industry.